PEMANTAUAN DEBIT AIR DAN SEDIMEN MELAYANG DI SUB DAS LEWARA DESA BALANE KECAMATAN KINOVARO KABUPATEN SIGI - Hari Gunawan; Naharuddin Naharuddin; Abdul Wahid (Universitas Tadulako, 2015)
Watershed as an ecosystem has survival benefit for humans and other living organisms, in which there is forest that has many services, such as: water management, flood control soil erosion protection, soil fertility maintainance, nutrient preservation and environmental balance conservation. Sub watershed Lewara is one of the sub-watershed that provide water supply in the watershed area of Palu. However, reduction on vegetation cover along the riverbank of Lewara lead erosin and increased the run off which is also a cause sedimentation. This study aimed to calculate water discharge and sediment drift produced by sub watershed of Lewara at Balane Village, Sub district of Kinovaro. The method used in the study is a field survey and measurement directly water discharge and sediment at the field through determination of three points in the upstream, midstream, and downstream. The results of the study indicate that water discharge and drift sediment concentration in the study period that discharge of water with an average value of 1,8506 m3/s and drift sediment concentration with an average rating of 0,000081 g/l. Based on the results obtained indicate water discharge has a strong corelation with the drift sediment total with correlation value of 0.621, and a strong correlation of rainfall and drift sediment total with the correlation value of 0.699. This may be concluded that the increased rainfall would be followed by increased water discharge and drift sediment load concentration by river flows. Keywords: watershed, water discharge, drift sediment